Composition and Pattern of Vegetation Distribution at the Tree Level in the Forest Area of Sorong Nature Tourism Park - Ponisri Ponisri; Fajrianto Saeni; Lona H. Nanlohy (Agrologia, 2021)
This study aims to determine the species composition, frequency, density, dominance, important value index (INP) and the distribution of tree species. The method used in this research is the Line Transect Plot Method. The total area of the sample plots is 1 ha (10.000 m2) with a total of 25 sample plots, which are placed purposively at the study site. Observational data were analyzed according to the parameters and described qualitatively and quantitatively and presented in the form of tabulations and pictures. The composition of vegetation types in the Sorong Nature Tourism Park forest contains 50 plant species, namely 30 known families and 3 plant species not yet traded, scientific and family names. The number of tree levels is 36 species with the largest density value (K) for resak (Vatica papuana) and guava (Syzygium, sp ) which is 29.81/ha with a Relative Density (KR) of 15.897% with the smallest density value (K). 0.962/ha, and the value of relative density (KR) was 0.5128%, respectively. The largest frequency (F) value is found in guava with a value of 0.731, relative frequency (FR) of 13.19%, and the lowest value of frequency (F) is 0.038 %, the smallest relative frequency (FR) is 0.694%. With the largest dominance value (C) in resak plants of 2,561 and relative dominance of 15.95%, while the lowest dominance was 0.033 and relative dominance was 0.208%. Where the highest Importance Value Index (INP) is on the guava tree at 43.117 and the lowest Important Value Index (INP) is in the Trichadenia tree, sp 1.3964. The distribution pattern at the tree level is based on the morista index, which is spread in groups or in clusters.Keywords: Composition, Vegetation, Nature Park